Adaptive error resilient video transmission over wide-band CDMA networks - Chuxiang Li; Jianhua Lu; Letaief, K.B. (IEEE VTS 53rd Vehicular Technology Conference, Spring 2001. Proceedings (Cat. No.01CH37202), 2001)
In this paper an efficient and reliable video transmission system is developed over wide-band CDMA wireless networks. The video coder is based on MPEG4 coding standard, while the transmission system is subject to a joint design of quantization, spreading, channel coding, as well as, an effective error concealment. In particular two-fold advantages of wide-band CDMA technology are considered. One is its effective mitigation of multi-path fading; the other is its potential in supporting variable data rate as a function of user application. Extensive simulations with different test video sequences and various channel conditions have confirmed the effectiveness of the proposed system.